2007
DOI: 10.1590/s0100-879x2006005000114
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a PPARG gene variant on obesity characteristics in Brazil

Abstract: The contribution of genetic factors to the development of obesity has been widely recognized, but the identity of the genes involved has not yet been fully clarified. Variation in genes involved in adipocyte differentiation and energy metabolism is expected to have a role in the etiology of obesity. We assessed the potential association of a polymorphism in one candidate gene, peroxisome proliferator-activated receptor-gamma (PPARGγ), involved in these pathways and obesityrelated phenotypes in 335 Brazilians o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
33
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 26 publications
3
33
1
Order By: Relevance
“…This sample has been originally designed to evaluate the impact of a nutritional intervention in the first year of life on the dietary quality of 3 to 4 years old children (20). Notwithstanding, it seems also to be a good source of information for genetic studies of the general southern Brazilian population, since allele and genotype frequencies observed in the present study were in the same range of those previously reported in European and European-derived populations, including the southern Brazilian population (5,7,10,14,40).…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations
“…This sample has been originally designed to evaluate the impact of a nutritional intervention in the first year of life on the dietary quality of 3 to 4 years old children (20). Notwithstanding, it seems also to be a good source of information for genetic studies of the general southern Brazilian population, since allele and genotype frequencies observed in the present study were in the same range of those previously reported in European and European-derived populations, including the southern Brazilian population (5,7,10,14,40).…”
Section: Discussionsupporting
confidence: 62%
“…A previous study in the same population found that the same allele contributing to higher BMI in adult males (10). There is still no consensus in the literature on the association between Pro12Ala genotypes and metabolic profile.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Population study in Europe, Africa and some parts of Asia revealed that these SNP's may be responsible for obesity leading to type 2 diabetes. [26][27][28] But all the results were not affirmative. 29 In the previous studies, T2D subjects were found to possess a significantly higher frequency of the Pro12 allele risk than non-diabetic controls, thus providing a supportive role for PPARg2 in the genetic risk for type 2 diabetes in French Caucasians.…”
Section: Discussionmentioning
confidence: 89%